The presence of mold in chestnut honey: Is a risk factor to health? - Cinar, Aycan (Parlar Scientific Publications, 2020)
In this study, 45 chestnut honey obtained from five different locations in Turkey were examined. The mycological results recovered 11 mold genera consisting of 79 isolates including Absidia spp., Alternaria spp., Aspergillus spp., Aureobasidium spp., Byssochlamys spp., Cladosporium spp., Eurotium spp., Fusarium spp., Mucor spp., Paecilomyces spp., Penicillium spp. The most predominant genera were Penicillium with 41.77 % followed by Aspergillus spp., 26.59 %, Cladosporium spp., 12.66 %. Among Penicillium spp. on chestnut honey, the predominantly isolated species were P. echinulatum, P. glabrum and P. variable, respectively. The presence of molds such as Aspergillus, Alternaria, Fusarium and Penicillium isolated from chestnut honey, which are potential mycotoxin producers, might cause a risk to public health. Also, these molds may trigger indigestion, allergic respiratory illness and adverse effects on the immune system. On the other hand, the total number of mold ranged from 0 to 61 CFU/g. Our results show that Chestnut honey samples in this study have good microbiological and hygienic quality. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Chestnut honey; Health effects; Identification; Mold; isolation